COMPARISON OF FOSFOMYCIN TROMETAMOL WITH CIPROFLOXACIN FOR UNCOMPLICATED UTI DUE TO E.COLI IN WOMEN - budiono, heri; Hardjowijoto, Sunaryo; Djojodimedjo, Tarmono; Soebadi, Doddy M; Widodo, Agung Dwi Wahyu; Budiono, Budiono (Indonesian Journal of Urology, 2015)
Objective: To compare clinical therapeutic effects (frequency, dysuria, and pyuria), microbiology, pharmacokinetics index Cmax/MIC Fosfomycin Trometamol 3 gr single dose with Ciprofloxacin 2 x 500 mg/12 hours for 5 days in the treatment of uncomplicated UTI in women due to Escherichia coli (E.Coli). Materials & Methods: Experimental observational design from February until July 2013. Twenty two women with uncomplicated UTI due to E.Coli performed clinical and microbiological examination. Pharmacokinetics index (Cmax/MIC) is looked for. Patients are divided 2 group, Ciprofloxacin 500 mg/12 hours 5 days and Fosfomycin Trometamol single dose. Repeat clinical and microbiological evaluation is performed in 7 days after therapy. Statistic analysis use Chi Square test, Paired T test, and Independent T test. Results: In the treatment of uncomplicated UTI in women, Fosfomycin Trometamol single dose therapy provides clinical cure (dysuria 81.2%, p = 0.338, frequency 90.9%, p = 0.004, pyuria 90.9%, p = 0.009) much better than Ciprofloxacin 500 mg/12 hours 5 days. Fosfomycin Trometamol single dose therapy also provides bacteriological eradication (100%) better than Ciprofloxacin 500 mg/12 hours 5 days (p = 0.035). Fosfomycin Trometamol single dose had a higher pharmacokinetics index (Cmax/MIC) compared to Ciprofloxacin 500 mg/12 hours (p = 0.035). Conclusion: Fosfomycin Trometamol single dose therapy is superior to Ciprofloxacin 500 mg/12 hours 5 days in the treatment of uncomplicated UTI in women. Keywords: Therapeutic effect, fosfomycin trometamol, ciprofloxacin, uncomplicated UTI, Escherichia coli.